2021
DOI: 10.1186/s13054-021-03560-2
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Ventilator-associated pneumonia in critically ill patients with COVID-19

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 2 publications
(2 reference statements)
4
25
0
Order By: Relevance
“…Little is known about the epidemiology of VAP in COVID- 19 patients. An European multicenter study including 568 cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection reported that the VAP incidence and ventilator-acquired tracheobronchitis were higher compared with the general population and influenza patients undergoing mechanical ventilation and reported that the majority of bacteria responsible for VAP were Gram-negative (Pseudomonas aeruginosa, Enterobacter species, and Klebsiella species) (16); similar results were found in the study reported by Maes et al (17) or Blonz et al (18). These concordant studies indicate that the incidence of VAP among COVID-19 patients is higher than that would be expected from other viral pneumonia.…”
supporting
confidence: 73%
“…Little is known about the epidemiology of VAP in COVID- 19 patients. An European multicenter study including 568 cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection reported that the VAP incidence and ventilator-acquired tracheobronchitis were higher compared with the general population and influenza patients undergoing mechanical ventilation and reported that the majority of bacteria responsible for VAP were Gram-negative (Pseudomonas aeruginosa, Enterobacter species, and Klebsiella species) (16); similar results were found in the study reported by Maes et al (17) or Blonz et al (18). These concordant studies indicate that the incidence of VAP among COVID-19 patients is higher than that would be expected from other viral pneumonia.…”
supporting
confidence: 73%
“…higher VAP incidence rates: United Kingdom (10): 28 per 1,000 ventilation days; Italy (11): 26 per 1,000 ventilation days; in fact, the hazard ratio shown in Maes et al (10) (2.01; 95% CI, 1.14-3.54; p = 0.001) was similar to that from Vacheron et al (9).…”
supporting
confidence: 60%
“…We found that invasive ventilation was a relevant risk factor for CAPA which is known as important risk factors for ventilator-associated pneumonia (VAP) in general [44]. Nevertheless, one study compared ventilated COVID-19 patients with non-COVID-19 ventilated patients and found an increased incidence overall of VAP (including CAPA) associated with COVID-19 [45]. Another author then suggested early prophylaxis with antifungal agents for critically ill COVID-19 patients [22].…”
Section: Other Risk Factorsmentioning
confidence: 99%